Has the pandemic paradoxically opened a new door in oncological care: are virtual tumour boards the next step? - Muhammad Abdul Rehman; Tahir, Erfa; Rao, Urooba Jawwad (Journal of the Pakistan Medical Association, 2022)
Respected editor, Multidisciplinary tumour board (MTB) meetings where patients’ cases discussed, and management plans are drawn by a consensus among participating physicians have become a standard of oncological practice globally (1, 2). Studies conducted through the past decades have amply demonstrated that MTB meetings lead to improved 5-year survival, and improved staging, diagnosis, adherence to oncological guidelines, and quality of life (3). Despite a few functional MTBs, such as the weekly City Tumor Board in Karachi, Pakistan has failed to ensure the formation of site-specific MTBs, a matter of great importance in cancer care countrywide (4). One big hurdle in the establishment and continuation of MTBs is the lack of time in the schedules of participating physicians (4). The COVID-19 pandemic has introduced changes in patient management, particularly in virtual MTBs (VMTB), which could potentially counter this challenge. The pandemic has had a massive impact on oncological care. A study collecting responses from more than 350 centers across 54 countries reported that 88.2% of centres saw a decrease in usual patient care (5). However, many hospitals and healthcare centres employed VMTBs to preserve optimal decision-making with restricted care. The study reported that, based on income stratification, 86.5% of high-income, 72.8% of middle-income, and 22.2% of low-income countries adopted VMTBs (5). The VMTBs improve coordination, decrease diagnosis or treatment delays, reduce travel expenditure, discuss more cases, and increase participant attendance (2). A survey revealed that of the respondents who attended VMTB meetings, 57.9% preferred VMTBs over in-person MTBs (2). The shift has been so beneficial that 78.9% preferred to continue VMTBs once social restrictions ended, and 60.4% believed VMTBs could become permanent (2, 5). The positive impact of the transition from in-person to virtual MTBs on feasibility, interdisciplinary coordination, and education of medical trainees has been further corroborated by other studies conducted during the pandemic (1). For countries struggling to establish and operate in-person MTBs, the pandemic has paradoxically unveiled an opportunity to circumvent the hurdle by highlighting the feasibility of VMTBs. Although VMTBs increase presentation lengths, require a technical setup and reduce interpersonal communication, the benefits of VMTBs far outweigh these hurdles (1, 2). For Pakistan, where there is a lack of in-person MTBs, the switch to VMTBs could ease and hasten the transition to a model of oncological care on par with international standards.